2019
DOI: 10.1021/acs.jmedchem.9b00446
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Targeting Anaplastic Lymphoma Kinase (ALK)

Abstract: As a receptor tyrosine kinase of insulin receptor (IR) subfamily, anaplastic lymphoma kinase (ALK) has been validated to play important roles in various cancers, especially anaplastic large cell lymphoma (ALCL), nonsmall cell lung cancer (NSCLC), and neuroblastomas. Currently, five small-molecule inhibitors of ALK, including Crizotinib, Ceritinib, Alectinib, Brigatinib, and Lorlatinib, have been approved by the U.S. Food and Drug Administration (FDA) against ALK-positive NSCLCs. Novel type-I1/2 and type-II ALK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 178 publications
0
88
0
Order By: Relevance
“…Indeed, we found that inhibition of insulin signalling with GSK1838705A blocked the stimulating effect of 20 µM urolithin C on glucose-induced ERK1/2 as its phosphorylation level returned to 8.3 mM glucose control value. It is worth mentioning that GSK1838705A inhibits the closely related IR and IGF-1R as well as anaplastic lymphoma kinase (ALK) which is also a member of the IR subfamily [37,38,51]. Nonetheless, INS-1 cells express IR but are likely lacking IGF-1R [36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that inhibition of insulin signalling with GSK1838705A blocked the stimulating effect of 20 µM urolithin C on glucose-induced ERK1/2 as its phosphorylation level returned to 8.3 mM glucose control value. It is worth mentioning that GSK1838705A inhibits the closely related IR and IGF-1R as well as anaplastic lymphoma kinase (ALK) which is also a member of the IR subfamily [37,38,51]. Nonetheless, INS-1 cells express IR but are likely lacking IGF-1R [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a VHL-recruiting ALK PROTAC based on brigatinib, named SIAIS117, was found to be more potent than brigatinib in inhibiting the growth of G1202R mutant ALK-expressing 293T cells by inducing G1202R mutant ALK degradation [ 52 ]. The PROTACs against ALK have also been briefly discussed in a review by Kong et al [ 53 ].…”
Section: Protacs Against Hematologic Malignanciesmentioning
confidence: 99%
“…Additional PROTACs targeting other components of the transcription machinery include those based on inhibitors of CDK9 or SMARCA2/4 [ 45 49 ]. PROTACs based on inhibitors targeting ALK or CDK6 kinases or based on inhibitors of the BCL6, BCL-XL or MCL1 apoptotic machinery components have also been developed [ 50 55 ]. Supplementary Table 2 shows a complete list of PROTACs explored in preclinical studies.…”
Section: Development Of Protacsmentioning
confidence: 99%